Implementasi Kebijakan Pengadaan Dokter Spesialis di Rumah Sakit Umum Daerah Kabupaten Natuna - Primawati, Titin; Madya, Faizal; Priyanto, Agus (Syntax Corporation, 2025)
Efforts to improve health services in the archipelago, border and outermost areas such as Natuna Regency is to distribute health workers evenly according to needs, the problem of the distribution of specialist doctors is still an issue in the health system in Natuna Regency, especially at the Natuna Regency Hospital, namely the availability of specialist doctors at the Natuna Regency Hospital for 4 basic services as many as 5 specialist doctors from the supposed availability of 8 doctors specialists according to the standard needs of the Ministry of Health. The purpose of this study is to find out how the implementation of the policy of procuring specialist doctors at the Natuna Regency Hospital and the factors that hinder the implementation of the policy of procuring specialist doctors at the Natuna Regency Hospital. This research method is a descriptive research with a qualitative approach, with data collection procedures through secondary data collection, observation and in-depth interviews with six (6) informants, namely the Head of the Health Office, the Director of the Hospital, the Head of BKPSDM, the Head of BP3D, the Head of BKPSDM and Specialist Doctors. The analysis technique used is to analyze primary data and secondary data. The results of this study can be seen that the supporters that affect the policy of procuring specialist doctors in Natuna Regency include the interests that are affected, the benefits of the policy, the implementers of the policy program, the existence of commitment, the existence of power, interests and strategies of the policy implementers, the characteristics of the institution and the ruler, the compliance and responsiveness of the policy implementers, the planned and funded action programs, and communication in the implementation of the policy of procurement of specialist doctors. Meanwhile, the inhibiting factors in the implementation of the policy of procuring specialist doctors include communication transmission, bureaucratic structure, and the absence of policy derivatives in the Natuna Regency area.